Bringing the lab to the field: a new lowland Microparmarion semi-slug (Gastropoda: Ariophantidae) described and DNA-barcoded in the forest. (17th November 2018) - Schilthuizen, Menno; Clavera, Anna Pazos; Khoo, Min Sheng; Bondar, Carin A; Elder, Charles H S; Bouma, Aglaia M; Eddington, Taly D; Reisinger, Christian; Cosentino, Emanuela; Rossato, Marzia; Delledonne, Massimo
Abstract: Cybertaxonomy and portable DNA sequencing now make it possible for citizen scientists to be engaged in the discovery and description of new taxa. We here provide a proof of principle. A new semi-slug, Microparmarion exquadratus n. sp. (Ariophantidae) was discovered during a field course in tropical biology in Borneo for citizen scientists. The new species is the first lowland representative of its genus. It differs from other (high-elevation) Microparmarion species by its size, pigmentation on head and tail, and shape of dart sac and receptaculum. As part of the course programme, the participants prepared a taxonomic description and illustrations, and used the mobile genomic laboratory of the course to obtain DNA barcodes. As far as we are aware, this is the first time a new invertebrate species has been described both morphologically and genetically from the field.